2021
DOI: 10.3389/fped.2021.714120
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Eating Habits and Sedentary Behavior During the COVID-19 Pandemic in Adolescents With Chronic Conditions

Abstract: Introduction: Among healthy adolescents, school closures and home confinement were shown to increase unhealthier eating habits and sedentary behavior. It remains unknown to which extent the pandemic has impacted the lifestyle of adolescents with chronic conditions. Thus, the aim of this study is to report on the impact of the COVID-19 outbreak on eating habits and sedentary behavior among adolescents with multiple chronic conditions (n = 347) from a tertiary, referral hospital vs. healthy peers.Methods: This o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…“Convenience food” was considered processed food in this study. Three studies showed a decrease ( 22 , 39 , 42 ), and two showed no change in consumption of processed food ( 21 , 25 ). The authors noted that the consumption of fast foods was reduced after “stay-home” orders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…“Convenience food” was considered processed food in this study. Three studies showed a decrease ( 22 , 39 , 42 ), and two showed no change in consumption of processed food ( 21 , 25 ). The authors noted that the consumption of fast foods was reduced after “stay-home” orders.…”
Section: Discussionmentioning
confidence: 99%
“…Confinements and stay-home orders led to positive changes in daily lifestyle, one of which was the increased consumption of home-cooked meals ( 2 , 20 , 29 , 42 ). Closure of shops, malls, and restaurants or limited open hours have made respondents shift to home-cooked meals ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social distancing measures may be even more restrictive to adolescents with immunocompromised conditions, as they are deemed to be at a higher risk of severe disease ( 4 ), and as routine changes, modifications to dietary habits and quality may be even more significant. However, the clinical impact of changes in eating habits during the pandemic is still controversial, as both positive (i.e., participation in home-cooking, eating with others) and negative (i.e., snacking, eating in front of television) changes have been observed ( 5 , 6 ). Indeed, a previous study from our group showed that adolescents with immunosuppressed chronic conditions changed their eating habits during the COVID-19 pandemic, cooking and consuming more home-made meals, but also eating more in front of the TV ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical impact of changes in eating habits during the pandemic is still controversial, as both positive (i.e., participation in home-cooking, eating with others) and negative (i.e., snacking, eating in front of television) changes have been observed ( 5 , 6 ). Indeed, a previous study from our group showed that adolescents with immunosuppressed chronic conditions changed their eating habits during the COVID-19 pandemic, cooking and consuming more home-made meals, but also eating more in front of the TV ( 5 ). These dietary habits may modify diet quality.…”
Section: Introductionmentioning
confidence: 99%